2001
DOI: 10.1117/12.435487
|View full text |Cite
|
Sign up to set email alerts
|

<title>Automated results notification system for PACS</title>

Abstract: Purpose: The purpose of this study was to determine if the interval between an examination being ordered by an Emergency Department physician and his or her review of the report and images could be shortened by notifying the physician that the results were available. This hypothesis was based on work done previously in the Medical Intensive Care Unit that showed that physicians would wait to review results for a time considerably longer than the time required for the radiologist to review the images and provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This has been noted in previous studies which have proposed that an appropriate "flag" may be required in order to alert clinicians. [10,12,17,25,26] Overall, the comments from participants were very positive and participants consistently commented that they felt that the notification system was very beneficial especially with regard to optimising time efficiency. None of the participants felt that the notification was either detrimental or intrusive and many stated that they felt more confident knowing that they were going to be "reminded" about an investigation that they may have requested a number of hours previously.…”
Section: Advantages Of Early Clinician Notificationmentioning
confidence: 90%
“…This has been noted in previous studies which have proposed that an appropriate "flag" may be required in order to alert clinicians. [10,12,17,25,26] Overall, the comments from participants were very positive and participants consistently commented that they felt that the notification system was very beneficial especially with regard to optimising time efficiency. None of the participants felt that the notification was either detrimental or intrusive and many stated that they felt more confident knowing that they were going to be "reminded" about an investigation that they may have requested a number of hours previously.…”
Section: Advantages Of Early Clinician Notificationmentioning
confidence: 90%
“…The 14.9-min reduction in the mean time to results encounter was the largest of the three metrics; however, this difference was not found Breakdown of ED residents' access methods for wet-reads during the PDA evaluation period. The percentages indicate the amount of the time they felt they used a specific means for obtaining wet-reads 0% 1Y25% 26Y50% 51Y75% 76Y100% PDA 3 3 1 2 PACS 2 7 Printouts 7 2 Other comments (both positive and negative) regarding the wet-read PDA application (1) I actually like to view the films (2) Great when worked (3) I always want to look at the actual films, so using wet-read PDA was best at notifying me that readings are actually available (4) Not as useful as you still need to see the actual film (2) Yes, orders could be on them and nurses could use them (3) Yes (4) Yes, but better in inpatient setting (5) This can potentially be used by the nursing staff, however, it may be more practical if the patient list can be customized to only those for whom the nurse cares be statistically significant (0.063). This detail can be explained by the large variances of both datasets (SD = 104.8 and 54.6 for the fax and PDA periods, respectively; see Table 1) caused by a number of Boutliers^.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the wet-read module contains a quality assurance (Q/A) component for tracking the performance of residents and fellows who generate wetreads during on call readout. Because it has been shown that the use of mobile computing technologies can facilitate the communication of radiological exam results to the requesting physician in an urgent care setting, 3,4 the wet-read module was extended to provide access to wet-reads and radiology reports at the point of care using wireless enabled personal digital assistants (PDAs) with the expectation that the physician's first encounter with the radiology results via the PDA would be faster than the original fax-based procedure. This paper describes the extension of the wet-read module and provides an assessment of its performance versus the original fax-based procedure.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Because of the high volume of ED cases at our institution, however, we decided to reserve pages for a subset of ED cases that are particularly urgent or have a high possibility of going unnoticed and unread by the radiologist, namely trauma cases, cases marked Bstat^by the ordering clinician, or teleradiology cases.…”
Section: Workflow Considerationsmentioning
confidence: 99%